Can Irisin be a New Agent Responsible for the Development of Heart Attack and Cardiac Cachexia? - Suna Aydin (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Cardiac cachexia, a syndrome characterized by systemic destruction, nutritional impairment and weight loss [1], has a prevalence ranging between 8 and 42% around the world [2]. The syndrome was first described by the father of medicine, Hippocrates, as follows: "the flesh is consumed and becomes water; shoulders, clavicles, chest and thighs melt away. The illness is fatal" [3]. Currently the most widely accepted description of primary cachexia is, in the presence of congestive heart failure, nonvoluntary loss of >6% of non-edematous body weight in less than 6 months [1,3,4]. Although the pathophysiological changes causing cardiac cachexia have not been fully clarified since the time of Hippocrates, it is suggested that nutritional impairment, gastrointestinal disorders, anabolic and catabolic imbalance, and neurohormonal and immune anomalies play a significant role in its development [1]. In addition to these major mechanisms, this perspective will focus on the possible role of irisin in the development of cardiac cachexia and heart attack.